Eosinophilic peritonitis induced by sucroferric oxyhydroxide. Issue 4 (July 2020) - Minato, Saori; Miyazawa, Haruhisa; Kitano, Taisuke; Shindo, Mitsutoshi; Ito, Kiyonori; Ueda, Yuichiro; Hirai, Keiji; Hoshino, Taro; Ookawara, Susumu; Morishita, Yoshiyuki
A 49-year-old woman developed eosinophilic peritonitis 2 months after starting continuous ambulatory peritoneal dialysis because of congenital right kidney hypoplasia and chronic glomerulonephritis. This was shown to have been induced by sucroferric oxyhydroxide, an iron-based phosphate binder, using a drug-induced lymphocyte stimulation test. Her eosinophilic peritonitis was improved after stopping the administration of sucroferric oxyhydroxide without providing any immunosuppressive agents.